Differences in Pediatric Non-Interventional Radiology Procedural Sedation Practices and Adverse Events by Registered Nurse and Physicians - Crego, Nancy (J Pediatr Nurs, 2016)
PURPOSE: The purpose of this study was to determine differences in sedation-related adverse events according to the type of provider monitoring and delivering sedation. DESIGN AND METHODS: A retrospective, cross-sectional, correlational design using secondary data from the Pediatric Sedation Research Consortium database was used for this study. RESULTS: A sample of 36,352 cases (0 to 14 years of age) sedated for diagnostic radiology procedures by three types of providers (registered nurses [RNs] alone, physicians (MDs) alone, or registered nurse + physician [RN+MD sedation teams]) were compared. Patients sedated by RNs alone or MDs alone had lower odds of unanticipated adverse events (odds ratios 0.46 and 0.53, respectively; p<0.0001) compared with RN+MD sedation provider teams. CONCLUSIONS: Team skills may be an important competency for RN+MD sedation teams in the non-interventional radiology setting. PRACTICE IMPLICATIONS: This study can inform clinicians, administrators, and quality-improvement managers of the differences in adverse event outcomes of pediatric radiology procedures when RN+MD teams provide sedation compared with RNs or MDs alone.